Mergers and Acquisitions as a Growth Strategy : Success Factors and Pitfalls - Kukkonen, Niko (My University, 2025)
The purpose of this thesis is to study mergers and acquisitions as a growth strategy and to find out which factors influence their success. In particular, it is examined what kinds of strategic, fi-nancial, and organizational factors distinguish successful acquisitions from unsuccessful ones and what challenges can prevent the achievement of expected synergy benefits. The efficiency of mergers and acquisitions has been discussed extensively in previous literature. According to traditional economic theory, mergers and acquisitions create value by combining resources and improving efficiency. On the other hand, more critical perspectives have highlighted challenges related to integration and the alignment of corporate cultures, which can interfere with the success of acquisitions. Previous studies show that strategic fit, careful due diligence process, and effective integration are key prerequisites for the success of acquisitions. However, many mergers and acquisitions fail due to the overestimation of synergies, cultural differences, and challenges related to manage-ment. Although mergers and acquisitions can at best offer significant growth opportunities, they involve considerable risks, and a failed acquisition can lead to financial losses and weakened com-petitiveness.

Tämän tutkielman tarkoitus on tutkia yritysostoja ja yritysjärjestelyjä kasvustrategiana sekä sel-vittää, mitkä tekijät vaikuttavat niiden onnistumiseen. Erityisesti tarkastellaan, millaiset strategi-set, taloudelliset ja organisatoriset tekijät erottavat onnistuneet yritysostot epäonnistuneista ja mitkä haasteet voivat estää odotettujen synergiaetujen saavuttamisen. Yritysostojen tehokkuutta on käsitelty laajasti aiemmassa kirjallisuudessa. Perinteisen talousteori-an mukaan yritysostot luovat arvoa yhdistämällä resursseja ja parantamalla tehokkuutta. Toisaalta kriittisemmissä tarkasteluissa on nostettu esiin integraatioon ja yrityskulttuurien yhteensovittami-seen liittyvät haasteet, jotka voivat häiritä yrityskauppojen onnistumista. Aiemmat tutkimukset osoittavat, että strateginen yhteensopivuus, huolellinen due diligence -prosessi ja tehokas integraatio ovat keskeisiä edellytyksiä yrityskauppojen onnistumiselle. Kuiten-kin monet yritysostot epäonnistuvat synergioiden yliarvioinnin, kulttuurierojen ja johtamiseen liittyvien haasteiden vuoksi. Vaikka yritysostot voivat parhaimmillaan tarjota merkittäviä kasvu-mahdollisuuksia, ne sisältävät huomattavia riskejä ja epäonnistunut yritysjärjestely voi johtaa ta-loudellisiin tappioihin ja heikentyneeseen kilpailukykyyn.
Keywords: corporate acquisitions; success factors; synergy; mergers; growth; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|; Rahoitus